2014 IEEE Energy Conversion Congress and Exposition (ECCE) 2014
DOI: 10.1109/ecce.2014.6953763
|View full text |Cite
|
Sign up to set email alerts
|

Design of Class E resonant rectifiers and diode evaluation for VHF power conversion

Abstract: Abstract-Resonantrectifiers have important applications in very-high-frequency (VHF) power conversion systems, including dc-dc converters, wireless power transfer systems, and energy recovery circuits for radio-frequency systems. In many of these applications, it is desirable for the rectifier to appear as a resistor at its ac input port. However, for a given dc output voltage, the input impedance of a resonant rectifier varies in magnitude and phase as output power changes. This paper presents a design method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Recently, several papers reported that the design of the class-E rectifier with low output-filter inductance. Even though the harmonic components are included in the output-filter inductance current, the performance improvement, such as pure resistive input impedance, can be obtained by considering low output-filter inductance [10,24,25]. Additionally, by enabling to use the output-filter inductance as a design parameter, a designer has one more degree of freedom for the class-E rectifier designs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several papers reported that the design of the class-E rectifier with low output-filter inductance. Even though the harmonic components are included in the output-filter inductance current, the performance improvement, such as pure resistive input impedance, can be obtained by considering low output-filter inductance [10,24,25]. Additionally, by enabling to use the output-filter inductance as a design parameter, a designer has one more degree of freedom for the class-E rectifier designs.…”
Section: Introductionmentioning
confidence: 99%
“…The Class-E resonant rectifier [25] with a quasi-resistiveinput is used as a starting point. Although this solution is able to reduce the reactive part of Z RX , by a proper choice of C D and by allowing for a ripple of the output current by reducing L C , it results in a output voltage strongly dependent on the dc load, which is not an acceptable solution for the system under consideration.…”
Section: Rectifier and Complete Dc-to-dc Linkmentioning
confidence: 99%
“…class F -1 or just generally harmonically-terminated PAs operated as rectifiers [22]. A promising design methodology for Class-E rectifiers with near resistive input impedance has been recently presented in [23]. Experimentally evaluated with Si Schottky diodes for VHF rectification, it may be perfectly valid for transistor-based topologies at UHF and the lower microwave bands.…”
Section: A Class-e Rectifiersmentioning
confidence: 99%